Protein-Based Silver Nanoparticles: Synthesis, Characterization, Administration, and Nanomedicine Applications - Syed Muhammad Hasan; Saadat Hussain; Muhammad Yousuf; José Agustín Tapia-Hernández; Daim Asif Raja (International Journal of Biomaterials)
Nanotechnology has emerged as a transformative field in recent years, greatly impacting medicine and healthcare with innovative solutions for complex diseases. Among these advancements, protein-based metal nanoparticles have shown exceptional promise in treating chronic illnesses, owing to their high biocompatibility, biodegradability, customizable surface properties, and precise drug delivery capabilities. Recent studies have highlighted advancements in targeting efficiency and controlled release, alongside the ability of protein-based metal nanoparticles to bypass the first-pass metabolism, enhancing bioavailability through novel administration routes. Cutting-edge research has also focused on functionalizing protein nanostructures with therapeutic metal ions, particularly silver, with a longstanding antimicrobial and anti-inflammatory history. New combinations of silver with protein-based nanoparticles are now showing significant potential in managing chronic and life-threatening conditions. This review provides a comprehensive overview of the latest synthesis methods, toxicity assessments, therapeutic applications, administration pathways, and advanced characterization techniques for protein-based silver nanoparticles, addressing the evolving landscape of nanomedicine.